THE GROWTH OF ISLAMIC BANKING IN INDONESIA - Fitriasari, Fika (Faculty of Economics and Business, University of Muhammadiyah Malang, 2012)
This article describes the growth of Islamic banking industry in Indonesia.Islamic banking to perform progressive and strong performance from thebanking indicators. Bank Indonesia estimates that the Islamic banking industry will achieve a growth higher than the national banking system in general. In the development of Islamic banking there are still some challenges to be solved especially for a small market share, lack ofhuman resources, and the lack of product development